Development of fish gelatin film for anti-fogging mushroom packaging - Azmi, Nazatul Shima; Kadir Basha, Roseliza; Othman, Siti Hajar; P. Mohammed, Mohd Afandi; Wakisaka, Minato; Ariffin, Siti Hajar; Salim, Nur Hafizah (Elsevier, 2025)
Mushrooms are extremely perspiring and transpiring commodities. The commonly used plastic films for packaging fresh mushrooms have lower water vapour permeability compared to the rate at which mushrooms transpire, resulting in excessive moisture accumulation inside the package which leads to fogging. This study aimed to investigate the properties of a fish scale gelatin-based film and its correlation with antifogging properties. To produce the gelatin-based film, gelatin was extracted from fish scales using chemical pretreatment and thermal denaturation of collagen. A film-forming solution (FFS) was prepared by dissolving 2% (w/v) gelatin in a solvent, with the addition of glycerol. The solution was then cast to form the film, which underwent tests for mechanical strength, thermal behaviour, barrier properties, and antifogging performance. The resulting film (G-Gly) exhibited reduced tensile strength (13.21 MPa) but increased elongation at break (82.4%). Differential scanning calorimetry revealed a lower glass transition temperature (59.91 °C) for G-Gly. Both gelatin films displayed high water vapour permeability (1.69–3.09x10-6 g m/m2.day.Pa), preventing condensation. Notably, the G and G-Gly films remained fog-free even under varying temperatures, unlike linear low-density polyethylene film (LLDPE). In conclusion, the gelatin-based films demonstrated strong barrier properties and effective antifogging capabilities, making them suitable for moisture-sensitive commodities like mushrooms.